Gender Differences in the Impact of Worklife on Executives’ Psychological Health - Mueller Marcus (Management)
The Impact of Worklife on Executives’ Psychological Health Purpose: This is the first scientific research studying the impact of worklife factors on executives’ psychological health by gender. The study has a particular focus on the factors of ‘Community’ and ‘Work-life balance’.